AN ANALYSIS OF TABOO WORDS AND EUPHEMISMS FOUND IN THE CHARACTERS’ UTTERANCES IN THE MOVIE ENTITLED “THE PURGE: ELECTION YEAR” - Mangantar Sitohang; sifa Cahayati; Mohamad Mansur (STIBA IEC JAKARTA, 2021)
The aims of this research are to find and to discuss the types, functions of Taboo words and the types of Euphemisms. The qualitative method is used in this research since the description regarding the utterances found in the movie is necessary. The quantitative approach is used in this research as well in representing the data findings by using percentages. The research data are taken from the movie scripts and are formed from the characters’ utterances either words or phrases. As the results, the researcher found five types of language of Taboo in the movie that consist of (1) Obscenity, (2) Epithets, (3) Profanity, (4) Insults and Slurs (5) and Vulgarity. Obscenity is the highest number of occurrence while Vulgarity holds the smallest number. There are four functions of Taboo language which are namely; (1) To draw Attention to one self, (2) To be Aggressive or Provocative, (3) To show Contempt, and (4) To mock Authority. To draw attention to one self is the most appeared functions of Taboo while to mock authority is the smallest number. There are four types of Euphemisms found in the movie which are (1) Euphemisms for Death and Killing, (2) Euphemism for Political Correctness, (3) Euphemisms for Sexual Activities, and (4) Euphemism for Addressing. The most appeared type of Euphemism is Euphemisms for Death and Killing while the least appeared one is Euphemism for Addressing.